2016
DOI: 10.5603/fm.a2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Morphological predictors of sleep apnoea severity

Abstract: (Folia Morphol 2016; 75, 1: 107-111)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“… 32 described the two divided segments of the E-tube, the muscles attached to the E-tube, and the seromucous glands under the epithelium, and discussed the possible mechanism of the opening and closure of the E-tube based on its musculature. Wysocki 33 elaborated the configurations and internal structures of the rat temporal bone, middle, and inner ear and measured the parameters of the external auditory, internal auditory meatus, auditory ossicles, tympanic cavity, and E-tube: most results were consistent with those of the present study. However, the fundamental purpose of this study was to perform E-tube angiography using an interventional method that can offer an optimal approach for further investigation of ETD treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 32 described the two divided segments of the E-tube, the muscles attached to the E-tube, and the seromucous glands under the epithelium, and discussed the possible mechanism of the opening and closure of the E-tube based on its musculature. Wysocki 33 elaborated the configurations and internal structures of the rat temporal bone, middle, and inner ear and measured the parameters of the external auditory, internal auditory meatus, auditory ossicles, tympanic cavity, and E-tube: most results were consistent with those of the present study. However, the fundamental purpose of this study was to perform E-tube angiography using an interventional method that can offer an optimal approach for further investigation of ETD treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The diameter, overall length, and length of the nasopharyngeal opening of rat E-tubes have been reported in several previous studies. 32 , 33 , 34 However, these studies have not indicated the measurement methods for these parameters, and several of the data are shown as approximate values. In the present study, the anatomical parameters of the E-tube were precisely measured using ImageJ software.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] A total of 39.2% of this study population had severe OSA, and mild and moderate OSA were 16.3% and 27.1% respectively (Table 3). Our study demonstrated that female patients with AHI > 15 showed no significant differences in the posterior airway space and soft palate length ( 24 In this study, we report that the male patients in AHI < 15 and AHI > 15 groups showed significant differences in the SPL. In contrast, the female patients showed no significant differences in SPL with increasing severity of OSA.…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 55%
“…20 In addition, a study that evaluated the relationship between the facial morphological features and the increasing severity of OSA demonstrated a significant connection between neck circumference and AHI in male patients with OSA in the stepwise regression model. 24 It was also reported that neck circumference and BMI were important predictors of OSA. [25][26][27] Rogers et al reported a similar finding in a study that BMI or waist circumference could be the predictors associated with the risk of OSA in the Black population.…”
Section: Ta B L Ementioning
confidence: 96%
“…This small parameter allows the microneedle to be inserted into the cochlea without fracture of the osseous spiral lamina, thus reducing modiolar injury. [ 29 ] The FM1‐43FX microneedles were prepared by codissolving PLGA copolymer and FM1‐43FX, a fixable fluorescent dye that behaves as a permanent blocker of the mechanotransducer channel, in DMSO (Figure 8D). The final concentration of the FM1‐43FX dye was 1% (w/w) of the PLGA.…”
Section: Resultsmentioning
confidence: 99%